Polarimetry of Saturnian satellite Enceladus - Zaitsev, S.V.; Kiselev, N.N.; Rosenbush, V.K.; Kolesnikov, S.V.; Shakhovskoy, D.N. (Advances in Astronomy and Space Physics, 2015)
We present results of polarimetric observations of Saturn's moon Enceladus carried out from April 14, 2010 to April 13, 2013 in WR spectral band (550-750 nm). We used 2.6-m telescope equipped with a one-channel photoelectric photometer-polarimeter (Crimean Astrophysical Observatory). The measurements were performed at phase angles ranging from 1.65° to 5.71°. The phase-angle dependence of linear polarization of Enceladus was obtained using the results of our observations. Results obtained are discussed in terms of existing models of light scattering by regolith surfaces.